2021
DOI: 10.3389/fpsyg.2021.624474
|View full text |Cite
|
Sign up to set email alerts
|

Singing Together, Yet Apart: The Experience of UK Choir Members and Facilitators During the Covid-19 Pandemic

Abstract: The Covid-19 induced United Kingdom-wide lockdown in 2020 saw choirs face a unique situation of trying to continue without being able to meet in-person. Live networked simultaneous music-making for large groups of singers is not possible, so other “virtual choir” activities were explored. A cross sectional online survey of 3948 choir members and facilitators from across the United Kingdom was conducted, with qualitative analysis of open text questions, to investigate which virtual choir solutions have been emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 40 publications
5
76
0
2
Order By: Relevance
“…This information illustrates that several financial, technological, and logistical factors need to be considered for a musical group to successfully adapt virtually. These issues were also explored in the study by Daffern et al (2021) of choir singers and facilitators during COVID-19 lockdown. These researchers identified that "Co-creation through Singing" was important to their respondents, who described "an overwhelming sense of loss of the embodied experience of singing together in realtime, which is unattainable from existing virtual choir models" (Daffern et al, 2021, abstract).…”
Section: Discussionmentioning
confidence: 99%
“…This information illustrates that several financial, technological, and logistical factors need to be considered for a musical group to successfully adapt virtually. These issues were also explored in the study by Daffern et al (2021) of choir singers and facilitators during COVID-19 lockdown. These researchers identified that "Co-creation through Singing" was important to their respondents, who described "an overwhelming sense of loss of the embodied experience of singing together in realtime, which is unattainable from existing virtual choir models" (Daffern et al, 2021, abstract).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the fact that values remained within non-pandemic ranges suggests some coping efficacy of virtual choirs and orchestras. Daffern et al (2021) describe three overall modes of virtual joint music making: (i) live-streamed where individuals sing or play with performances live-streamed via social media; (ii) live tele-conferencing where Zoom participants sing or play live to the sounds from a designated leader (with microphones muted); and (iii) multitrack where a collective end-product is mixed offline from solo tracks supplied by individuals. This last format was pioneered in 2009 by the American composer Eric Whitacre who also launched his "Virtual Choir 6: Sing Gently" with 40,0000 singers from 145 countries in 2020.…”
Section: Amateursmentioning
confidence: 99%
“…The disappointment experienced by many amateur musicians (Daffern et al, 2021;Morgan-Ellis, 2021) and the self-reported quantitative ceasing of singing activities (Kiernan et al, under review), in fact, suggest that whenever singing at home increased (Ferreri et al, 2021;Fink et al, 2021), this could have been primarily driven by those who did not sing before lockdown. Balcony singing offered a treasured way of restoring individual agency against an incapacitating health disaster (Deaville & Lemire, 2021).…”
Section: Amateursmentioning
confidence: 99%
“…Reminiscent of previous outbreaks such as “The Plague of Saint Charles” hitting Milan in 1576 (Chiu, 2020 ), daily routines involving balcony singing and joint, steadfast clapping for healthcare workers accompanied by loud vocalizations, whistling, and percussive use of kitchen utensils (Taylor, 2020 ) offered musical ways of imposing structure upon chaos and expressing gratitude through ritualistic behavior (Imber-Black, 2020 ). When music teaching moved online (Philippe et al, 2020 ; de Bruin, 2021 ), musical skills and social cohesion were nurtured through lockdown-compatible, video-conference-based rehearsal formats (Datta, 2020 ; Daffern et al, 2021 ; MacDonald et al, 2021 ). Governmental and private organizations commissioned and disseminated health information videos promoting hand-washing (Thampi et al, 2020 ) and similar protective measures through musical mnemonics and dance challenges.…”
Section: Introductionmentioning
confidence: 99%